Detection of Various Streptococcus spp. and Their Antimicrobial Resistance Patterns in Clinical Specimens from Austrian Swine Stocks - René Renzhammer; Igor Loncaric; Marisa Ladstätter; Beate Pinior; Franz-Ferdinand Roch; Joachim Spergser; Andrea Ladinig; Christine Unterweger (MDPI AG, 2020)
Knowledge of pathogenic potential, frequency and antimicrobial resistance patterns of porcine Streptococcus (S.) spp. other than S. suis is scarce. Between 2016 and 2020, altogether 553 S. spp. isolates were recovered from clinical specimens taken from Austrian swine stocks and submitted for routine microbiological examination. Antimicrobial susceptibility testing towards eight antimicrobial substances was performed using disk diffusion test. All isolates from skin lesions belonged to the species S. dysgalactiae subspecies equisimilis (SDSE). S. hyovaginalis was mainly isolated from the upper respiratory tract (15/19) and S. thoraltensis from the genitourinary tract (11/15). The majority of S. suis isolates were resistant to tetracycline (66%), clindamycin (62%) and erythromycin (58%). S. suis isolates from the joints had the highest resistance rates. S. suis and SDSE isolates resistant to tetracycline were more likely to be resistant to erythromycin and clindamycin (p < 0.01). Results show that different species of Streptococcus tend to occur in specific body sites. Nevertheless, a statement whether these species are colonizers or potential pathogens cannot be given so far. High resistance rates of S. suis towards tetracyclines and erythromycin and high recovery rates of S. suis from lung tissue should be considered when treating pigs with respiratory diseases.